bahasa inggrisPeningkatan keterampilan manipulatif anak usia 6 tahun melalui senam "Si buyung" - Galih Dwi, Galih Dwi; Maliki, Osa; Ari Widiyatmoko, Fajar; Hudah, Maftukin; Yuliawan, Dhedhy (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2024)
This study aims to determine the effectiveness of Si Buyung Gymnastics in improving the manipulative skills of learners aged 6 years. The research method used was an experiment, and the sample used was 15 learners. The manipulative skill test instrument is adapted from the basic motion skills test, which is the test of catching and bouncing the ball. The sampling technique used is purposive sampling, namely: (1) individuals who are willing to be subjects or permitted by parents or guardians; (2) kindergarten students; (3) 6 years old; and (4) students who are physically and spiritually healthy. Pretest and post-test data analysis techniques use paired T-test statistical techniques. The results showed that movement and song learning had an influence on improving the manipulative skills of kindergarten students; this was shown from the pretest and post-test results. The results of the statistical test T-paired pretest amounted to 16.67, while the post-test was 19.44. The paired T-test shows higher post-test results than the pretest. The results of the data analysis showed a real improvement in the students' ball-bouncing skills after being given the Si Buyung Gymnastics treatment.